Subjective wellbeing during adolescence: a literature review on key factors relating to adolescent's subjective wellbeing and education outcomes - Sabbiana Cunsolo (Firenze University Press, 2017)
Adolescence is a critical period of development, in which teenagers are continuously changing mentally, physically, and psychologically. They are learning more about the world and trying to strive for both parental independence and inclusion in social groups. The present paper covers recent literature on subjective wellbeing (SWB) among adolescents, aimed at measuring their emotional and retrospective cognitive evaluations of their own lives and identifying key factors that relate to SWB. Evidence shows the importance of the social dimension of life in shaping adolescent SWB. Parenting support, school contexts and school connectedness are among the most significant predictors of academic achievement and SWB.